The effectiveness of implemented interventions at the workplace to promote the mental health of working women: A systematic review - Zakieh Arab Najafabadi; Atefeh Vaezi; Negah Tavakolifard; Zahra Amini (Journal of Education and Health Promotion)
Over the last decades, a gradual increase in prevailing mental disorders in the adult population has been observed all over the world. Global estimates of anxiety, stress, depression, and mood disorders prevalence have also been high. Employed women are susceptible to experiencing some symptoms or mental disorders due to their lifestyle or working conditions. The objective of this study is to find effective interventions based on the workplace to improve the mental health of employed women. This systematic review was conducted by following PRISMA guidelines to report systematic reviews. The papers in Web of Science, Scopus, PubMed, and Google Scholar for English and SID, Magiran, and Irandoc for Persian resources were searched from 2005 to 2023. To include the final study, 15 papers were eligible to be selected. The findings of this study show that giving interventions to improve the mental health of employed women is hopeful and employers may promote their mental health through performing low-cost and effective intervention programs such as setting up supportive training groups’ sessions and group exercises. The outcomes of performing this study may help to increase our knowledge concerning the necessity of giving effective health interventions to women in the workplace and to consider the shortage of giving such interventions. Therefore, giving the interventions is recommended aiming at the health and welfare improvement of employed women.